Identification of Freshwater Prawns from the Embung AKAP in the Pekanbaru Bus Station, Riau - Rezzy Marprianti; Windarti Windarti; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractEmbung AKAP is a man-made lake located in the Pekanbaru bus station area. This lakeis inhabited by small sized prawns. Scientific information of that organism, however, is almost none. To understand the types of prawns present that area, a research has been conducted from February to March 2018. Prawn captured were conducted once/week for a month period, using a scoop net (mesh 0,5 cm). Morphometrical and meristical characteristics of the prawns were then analyzed descriptively. The prawns sampled of a single species only, namely Macrobrachium mammillodactylus, Thallwitz 1892 (Palaemonidae). This species characterized by schapocherite length that is shorter than rostrum length, rostral teeth sub-equally spaced, 7-9 teeth in the dorsal and 4 teeth in the ventral of rostrum. In male, rostrum, propodus, carpus, and merus are longer than those of the female.M. mammillodactylusis characterized by the presence of mammiliform setae in all over the body .Keywords : Man-made lake,Macrobrachium mammillodactylus, morphometrical characteristics, meristical characteristics,